Labour, Delivery and Perinatal Outcomes of Women with Advanced Maternal Age: A Comparative Study - EZEOKE, Grace; Fawole, Adegboyega; Bakare, Tola; OGUNLAJA, Olumuyiwa; JIMOH, Olanrewaju; ADENIRAN, Abiodun (AlQalam Journal of Medical and Applied Sciences, 2022)
Background. Although advanced maternal age (AMA) has been identified as a risk factor for adverse obstetric outcomes, research efforts continue to gather evidence to describe the relationship. Methods. This was a comparative study conducted at a tertiary health facility. Participants were pregnant women who delivered after viability (28 weeks gestation) at the facility over a ten year period categorized into those with advanced maternal age (>35 years) and younger women (≤35 years). The source of data was the hospital delivery records; data analysis was performed with SPSS version 21.0 while p-value <0.05 was significant. Results. The prevalence of AMA was 8.8% (761/8645), 18 (2.4%) were nulliparous, 351 (46.1%) had tertiary education, 196 (25.8%) had inter-pregnancy interval >24 months while 66 (8.7%) had preterm delivery. AMA was associated with significantly higher occurrence of obstructed labour (204 vs. 129; p0.001) and primary postpartum haemorrhage (208 vs. 123; p0.001). Onset of labour (OR 95%CI [0.470, 0.063-3.493]; p0.450), augmentation of labour (OR 95%CI [0.969, 0.830-1.132]; p0.695) and need for episiotomy (OR 95%CI [1.116, 0.955-1.303]; p0.166) were not statistically different for AMA compared to younger women. The caesarean section rates were 40.0% for AMA and 23.7% for younger women while perinatal mortality rates were 391/1,000 for AMA and 110/1,000 live births for younger women. Conclusion. Pregnancy outcome in women with AMA was poorer with about twice the caesarean section rate and thrice the perinatal mortality rate compared to younger women. Therefore, efforts should be made to limit pregnancy in women with AMA.